Clinical and video-polysomnographic analysis of rapid eye movement sleep behavior disorder and other sleep disturbances in dementia with Lewy bodies. Issue 7 (4th April 2019) - Fernández-Arcos, Ana; Morenas-Rodríguez, Estrella; Santamaria, Joan; Sánchez-Valle, Raquel; Lladó, Albert; Gaig, Carles; Lleó, Alberto; Iranzo, Alex
Abstract: Objective: The main objective of this study was to study rapid eye movement (REM) sleep behavior disorder (RBD) and other sleep disorders in dementia with Lewy bodies (DLB). Methods: Consecutive patients with DLB and mild dementia severity were recruited irrespective of sleep complaints. Patients underwent clinical interview, assessment of sleep scales, and video-polysomnography (V-PSG). RBD was diagnosed with V-PSG based on electromyographic and audiovisual analysis. Results: Thirty-five patients (65.7% men; mean age 77.7 ± 6.1 years) were evaluated. Poor sleep quality (54.3%), hypersomnia (37.1%), snoring (60%), and abnormal nocturnal behaviors (77.1%) were reported. Sleep–wake architecture abnormalities occurred in 75% patients and consisted of occipital slowing on awake electroencephalography (EEG; 34.4%), the absence of sleep spindles and K complexes (12.9%), slow frequency sleep spindles (12.9%), delta activity in REM sleep (19.2%), and REM sleep without atonia (44%). Three patients showed hallucinatory-like behaviors and 10 patients showed abnormal behaviors during arousals mimicking RBD. RBD was diagnosed in 50% of those patients in whom sufficient REM sleep was attained. Of these, 72.7% were not aware of displaying dream-enacting behaviors and in 63.7% RBD preceded the onset of cognitive impairment. For RBD diagnosis, the sensitivity of Mayo Sleep Questionnaire was 50%, specificity was 66.7%, positive predictive value was 83.3%, and negative predictive value was 28%. False-positive RBD cases according to clinical history had hallucinatory-like behaviors, severe obstructive sleep apnea, and prominent periodic limb movements in sleep. Occipital EEG frequency while awake and rate of electromyographic activity in REM sleep were negatively correlated, suggesting a common subcortical origin. Conclusion: In DLB, RBD and sleep–wake disorders are common, heterogeneous, and complex, challenging their identification without performing V-PSG.